A case of failed ‘rehabilitation’? The biopolitics and geopolitics of military intervention in Libya - Robson, Matthew (Universitas Islam Internasional Indonesia (UIII), 2024)
This paper interrogates the biopolitics and geopolitics of the Western-led military intervention in Libya of 2011. The Foucauldian concept ‘dispositif’ is deployed to grasp how a network of different international actors, practices, discourses, and technologies of power were oriented towards biopolitically securing the Libyan population prior to the intervention. The paper takes as an example the development practices of the United Nations Development Program (UNDP), which sought to secure the Libyan population through biopolitical technologies of governance like ‘human security’ and ‘human development’. The paper argues that it is the apparent failure of these efforts, as shown through stagnated democratization and liberalization under Muammar Gaddafi’s rule, which foregrounded the spectacular display of sovereign/biopower by Western governments during the military intervention. It is thus a failed ‘rehabilitation’ of the Libyan government, which led powerful Western governments to pursue their biopolitical and geopolitical objectives in Libya through more violent means.